Clinical outcomes after bare‐metal stenting in diabetic patients with lesions carrying a low risk of restenosis 1. Issue 1 (8th November 2012) - Woudstra, Pier; Damman, Peter; Beijk, Marcel A.M.; Grundeken, Maik J.D.; Harskamp, Ralf E.; Koch, Karel T.; Henriques, José P.S.; Baan, Jan; Vis, Marije M.; Piek, Jan J.; Tijssen, Jan G.P.; de Winter, Robbert J.
Abstract Objective To evaluate the clinical results of diabetic patients undergoing percutaneous coronary intervention (PCI) for coronary artery lesions carrying a low risk of restenosis treated with a bare‐metal stent (BMS). Background There is a discrepancy between current international guidelines on the use of BMS in diabetics with low risk of restenosis coronary artery lesions. Methods and Results Registry data from diabetic patients who underwent non‐urgent PCI in a high‐volume tertiary referral hospital in the Netherlands was used. The main outcomes were target lesion revascularization (TLR) and the composite of cardiac death, myocardial infarction, and target vessel revascularization at 1‐year of follow‐up. A total of 1, 951 patients were included, of which 1, 596 non‐diabetics (non‐DM), 231 non‐insulin requiring diabetics (NIRDM), and 124 insulin requiring diabetics (IRDM).TLR rates in non‐DM versus NIRDM were similar (6.3% vs. 5.6%; P = 0.68), whereas TLR in IRDM was higher (6.3% vs. 11.3%; P = 0.03). The composite of cardiovascular clinical outcomes was not significantly different in non‐DM versus NIRDM (9.5% vs. 13.4%; P = 0.07), though in IRDM the incidence was higher (9.5% vs. 17.7%; P < 0.01). Conclusion No differences were observed in TLR or composite clinical endpoint at 1‐year between non‐DM and NIRDM after BMS placement in coronary artery lesions carrying a low risk of restenosis. The presence of IRDM was associated with higher TLR rates when treated with BMS. These results imply that BMS placement may be considered in patients with NIRDM but further work is required to define treatment strategies and, more importantly, improve the outcomes in diabetics. © 2012 Wiley Periodicals, Inc.